2009
DOI: 10.1083/jcb.200903053
|View full text |Cite
|
Sign up to set email alerts
|

MURC/Cavin-4 and cavin family members form tissue-specific caveolar complexes

Abstract: Polymerase I and transcript release factor (PTRF)/Cavin is a cytoplasmic protein whose expression is obligatory for caveola formation. Using biochemistry and fluorescence resonance energy transfer–based approaches, we now show that a family of related proteins, PTRF/Cavin-1, serum deprivation response (SDR)/Cavin-2, SDR-related gene product that binds to C kinase (SRBC)/Cavin-3, and muscle-restricted coiled-coil protein (MURC)/Cavin-4, forms a multiprotein complex that associates with caveolae. This complex ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
295
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(323 citation statements)
references
References 55 publications
(124 reference statements)
19
295
1
2
Order By: Relevance
“…Genetic ablation of cavin-1 also led to a reduced content of cavin-3 and of all caveolins. Except for the maintained level of cavin-2 in the bladder, a finding that needs to be confirmed using additional antibodies, this is largely in keeping with recent work with other cavin-1-deficient tissues (Bastiani et al, 2009;. Pacsin2 was recently shown to be associated with caveolae and to play a role in their formation (Hansen et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Genetic ablation of cavin-1 also led to a reduced content of cavin-3 and of all caveolins. Except for the maintained level of cavin-2 in the bladder, a finding that needs to be confirmed using additional antibodies, this is largely in keeping with recent work with other cavin-1-deficient tissues (Bastiani et al, 2009;. Pacsin2 was recently shown to be associated with caveolae and to play a role in their formation (Hansen et al, 2011).…”
Section: Discussionsupporting
confidence: 55%
“…We sporadically found dead and rejected mice shortly after birth, but timed breeding needs to be undertaken to determine when the mice succumb and for what reason. The other published studies using this strain did not report increased embryonic/perinatal mortality (Bastiani et al, 2009;. If the increased mortality depends on background or breeding environment is not known.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The cavin family consists of four members, cavin1 to cavin4, that are required to stabilize the Cav1 proteins and to shape caveolae (16 -19). The cavins also have the ability to bind to PtdSer (16,17,20). Furthermore, a recent study demonstrated that there are 50 cavin1 molecules per caveola (15,21).…”
Section: Edited By Dennis R Voelkermentioning
confidence: 99%
“…Intriguingly, caveolae in adipocytes were suggested to produce TG (Ost et al 2005), which may also be transferred to LDs through the hemi-fusion channel. The functions of caveolins are closely linked to a family of cytoplasmic proteins termed cavins (Hill et al 2008;Bastiani et al 2009;Hansen et al 2009;McMahon et al 2009). PTRF/ cavin-1 is essential for the formation of caveolae (Hill et al 2008;Liu et al 2008) and, like caveolin, has been shown to be associated with LD function and lipid storage in cultured adipocytes (Aboulaich et al 2006), mice (Liu et al 2008), and human patients (Hayashi et al 2009;Rajab et al 2010).…”
Section: Interactions With Caveolae Caveolins and Cavinsmentioning
confidence: 99%